Sexuality after 60 years of age Sexualidad después de los 60 años - ESGUERRA VELANDIA IRENE (Universidad Nacional de Colombia, 2007)
The noticeable increase in the portion of the population that is over 60 years of age leads us to think in those aspects that have incidence in the quality of life of those adults and not just on morbidity and mortality figures. Sexuality of senior adults, as a quality of life indicator, requires greater understanding of those factors that have impact, over and beyond those changes in morphology and physiology. This article invites one to think of those factors and to contribute in eliminating myths regarding sexuality of humans in general and of senior adults in particular. El notorio incremento de la franja poblacional de personas mayores de 60 años lleva a pensar en todos aquellos aspectos que inciden en la calidad de vida de estos y no solamente sobre las cifras de morbimortalidad. La sexualidad de las personas mayores, como indicador de calidad de vida, requiere una mayor comprensión sobre todos aquellos factores que la afectan, más allá de los cambios morfofisiológicos. Este artículo invita a reflexionar sobre estos factores y a contribuir en la desmitificación de la sexualidad del ser humano en general y de las personas mayores en particular.